Credibility of Information Sources and Channels as Perceived by Paddy Farmers in Telangana State (Indian Journal of Extension Education, 2022)
This paper investigates perceived credibility of paddy farmers’ information sources and channels. The dissemination of agricultural information to farmers has been one of the crucial factors for the transmission of newer and relevant technologies. Farmers’ information needs are transforming to more need-based than demand-driven. A sum of 120 respondents was selected based on proportionate random sampling from two villages selected from each of the two blocks of Khammam district. Mean per cent score was used for obtaining the degree of credibility of sources and channels. Opinion leaders in personal localite sources, agricultural scientists in personal cosmopolite sources, result demonstration in personal cosmopolite channels and television in impersonal cosmopolite channels were perceived as highly credible by paddy farmers. One-third of respondents had high level of overall credibility.